TINGKAT KESADARAN PESERTA DIDIK TERHADAP MITIGASI BENCANA GEMPA BUMI DI SMA NEGERI 1 KRUENG BARONA JAYA - Trimunandar, Rizky; Abdi, Abdul Wahab; Desfandi, Mirza (Universitas Syiah Kuala, 2024)
Indonesia is an area prone to earthquakes, this is influenced by the location of Indonesia which is located on three active world plates, namely, the Eurasian Plate, the Pacific Plate, and the Indo-Australian Plate. This area has a very high potential for disasters such as volcanic eruptions, earthquakes, tsunamis, floods and landslides, especially in areas located on tectonic plate faults. Efforts to minimize risk or loss for humans require knowledge, understanding, preparedness skills to prevent, detect and anticipate early on various kinds of disasters or better known as disaster mitigation. The purpose of this study was to determine the level of awareness of students towards earthquake disaster mitigation at SMA Negeri 1 Krueng Barona Jaya. The population in this study amounted to 161 students, of the total population, 20 percent or as many as 32 respondents were taken as samples. Data collection is done by distributing questionnaires to students. The data processing technique uses quantitative methods and simple statistical formulas. Based on data processing from research on the Awareness Level of Students Against Earthquake Disaster Mitigation at SMA Negeri Krueng Barona Jaya, respondents who answered Yes 60% and answered No 40%. From these data, it can be concluded that most of the students of SMA Negeri 1 Krueng Barona have awareness of earthquake disaster mitigation.Keywords: Awareness, Students, Disaster mitigation, Earthquakes